Halal Computerised Systems Framework For The Halal Pharmaceuticals - Raja Rina, Raja Ikram (UTeM, 2013)
This research aims to develop a framework to address halal regulatory industry requirements for computerised systems in the pharmaceutical industry. Computerised systems and software technology are heavily used to improve manufacturing and supply chain performance. Industry and religious authorities require a documented guideline to enforce halal certification whenever a manual operation is substituted by a computerised system. This research provides a critical analysis on the existing system in three main areas. First, an analysis of computerized systems used throughout the pharmaceutical supply chain. Second, the identification of critical points and controls required in halal pharmaceuticals based on the guidelines of two countries - Malaysia and indonesia. Third, a review of existing regulatory requirements for Computerised Systems. A conceptual framework was designed and developed using the Hazard Analysis Critical Control Point (HACCP) method to identi fy critical control points that lead to haram conta mination. The initial framework was then validated via a review of Manufacturing Execution System (MES) implementation, a case study of an Enterpri se Resource Planning (ERP) implementation, a critical analysis of the international pharmaceutical industry standards, interview with subject matter experts and validation via prototype application. The outcome of this research would directly contribute to the gap in the current Halal Pharmaceuticals Guideline where usage of technology or computerised systems is not documented.